ISLAMIC ETHICS, SOCIAL PRACTICES, AND THE PRODUCTION OF PUBLIC SPACE: A SPATIAL SOCIOLOGY APPROACH TO URBAN QUALITY - Ahmadin; Ilham Samudra Sanur; Misbawati (Academic Bright Collaboration, 2026)
This study aims to analyze the role of Islamic ethics in shaping and transforming the quality of public space using a spatial sociology perspective. The unit of analysis is the relationship between ethical values, social practices, and the formation of urban public space. This aligns with recent studies on public space trends, which indicate a shift in focus from a normative approach to a critical-interdisciplinary approach that integrates spatial, cultural, and religious elements. This study employed a quantitative approach with survey data collected from 200 respondents living in various locations in Makassar. Data were analyzed using descriptive statistics and multiple linear regression to assess the influence of Islamic ethics and social practices on the quality of public space. The results of the study indicate that the level of Islamic Ethics (Mean = 4.12 – High) and Social Practices (Mean = 3.95 – High) are classified as high, while the Quality of Public Space is in the medium–high category (Mean = 3.78). The research instrument is declared valid (r > 0.30) and reliable (Cronbach's Alpha of 0.89; 0.87; and 0.85, respectively). The regression model also meets the assumptions of normality, linearity, freedom from multicollinearity, and homoscedasticity. The main findings indicate that Islamic Ethics (X) and Social Practices (Z) have a positive and significant effect on the Quality of Public Space (Y). This indicates that increasing the internalization of Islamic ethical values ​​and good social practices will be followed by an increase in the quality of public space. This study questions the importance of integrating ethical values ​​into urban planning and public space planning. This study finds that improving the quality of public space is not simply about strengthening public ethical awareness and social behavior, but requires an adequate institutional framework, spatial policies, and infrastructure. This study underscores the importance of integrating Islamic ethical principles into spatial sociology, emphasizing a relational model that connects values, social practices, and the production of public space. Furthermore, this study supports the global discourse on post-secular urbanism by highlighting the importance of Islamic ethics as a conceptual framework for developing inclusive and sustainable public spaces.